Kewenangan Dewan Pengawas Syariah Dan Implikasi Terhadap Perwujudan Corporate Social Responsibility Di Perbankan Syariah - Nury Khoiril Jamil; Robiatul Adawiyah; Rumawi Rumawi (SASI, 2021)
Every company has a social responsibility. There are measurements of social responsibility that are carried out to achieve usefulness, one of which is Islamic banking. Although Islamic banking is only considered a labeling issue. However, with the role of DPS which is realized through CSR, it indicates that Islamic banking contributes and is responsible for various social aspects and nation building as a common goal as stated in the 5th principle of Pancasila. This study aims to determine the authority of the Sharia Supervisory Board (DPS) as mandated in laws and regulations and the implications for the realization of Corporate Social Responsibility (CSR) in Islamic banking. This research method is normative juridical, with a statutory and conceptual approach that refers to legal doctrines. The results of the study indicate that DPS has an important role in preventive efforts for activities in Islamic banking as well as the actuality of social responsibility that is realized through CSR.